The Removal of Methylene Blue Dye from Aqueous Solutions Using Activated and Non-Activated Bentonites - Sameer Al-Asheh; Fawzi Banat; Leena Abu-Aitah (Adsorption Science & Technology)
An improvement in the adsorption capacity of naturally available bentonite towards water pollutants such as Methylene Blue dye (MBD) is certainly needed. For this purpose, sodium bentonite was activated by two methods: (1) treatment with sodium dodecyl sulphate (SDS) as an ionic surfactant and (2) thermal treatment in an oven operated at 850°C. Batch adsorption tests were carried out on removing MBD from aqueous solution using the above-mentioned bentonites. It was found that the effectiveness of bentonites towards MBD removal was in the following order: thermal-bentonite > SDS-bentonite > natural bentonite. X-Ray diffraction analysis showed that an increase in the microscopic bentonite platelets on treatment with SDS was the reason behind the higher uptake of MBD. An increase in sorbent concentration or initial pH value of the solutions resulted in a greater removal of MBD from the solution. An increase in temperature led to an increase in MBD uptake by the bentonites studied in this work. The Freundlich isotherm model was employed and found to represent the experimental data well.